2022
DOI: 10.1007/s00417-022-05946-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvascular density analysis in patients with rheumatoid arthritis treated with hydroxychloroquine

Abstract: Purpose Rheumatoid arthritis (RA) is the most common inflammatory joint disease, and hydroxychloroquine (HCQ) is an established treatment. The extent to which HCQ impacts ocular microvascular vessel density (VD) in patients with RA without evidence of HCQ retinopathy has not yet been conclusively clarified. The main aim of this study was to evaluate VD measured by optical coherence tomography angiography (OCTA) in patients with RA treated with HCQ. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Furthermore, this meta-analysis included studies that examined either patients with SLE or patients with rheumatoid arthritis, respectively. For rheumatoid arthritis, we could not demonstrate any influence of the disease on VD in OCT-A as stated in a previous publication [37]. This underlines that patients with different underlying diseases using HCQ should not be grouped when investigating the influence of HCQ on VD, as this could significantly bias the results.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Furthermore, this meta-analysis included studies that examined either patients with SLE or patients with rheumatoid arthritis, respectively. For rheumatoid arthritis, we could not demonstrate any influence of the disease on VD in OCT-A as stated in a previous publication [37]. This underlines that patients with different underlying diseases using HCQ should not be grouped when investigating the influence of HCQ on VD, as this could significantly bias the results.…”
Section: Discussionsupporting
confidence: 46%
“…In a previous study involving patients with rheumatoid arthritis and HCQ therapy, no difference in VD was observed between the patient group and the control group. Similarly, there was no correlation found between the cumulative HCQ dosage or duration of HCQ intake and VD [37]. This study, including a correlation analysis, uniquely comprised patients solely with rheumatoid arthritis and HCQ intake, excluding other autoimmune conditions where the disease itself could affect the microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-A is increasingly being used. The unique possibility of rapid and non-invasive imaging of blood vessels and the implication of common diseases like cardiovascular disease, diabetes mellitus and autoimmune diseases on the VD makes OCT-A a promising new technology in diagnosing and monitoring these disorders [36,[41][42][43]. It is therefore important that potential confounding factors influencing OCT-A measurement results are known and thus can be considered in the interpretation of measurement results in both scientific applications and in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The Signal Strength Index (SSI) is an important reference point for the image quality of the OCT-A measurement and for the validity of the quantitative OCT-A parameters [47]. In studies where OCT-A parameters are compared, usually only measurements with a SSI above a defined threshold are used to achieve a certain standard of validity, as it was done in this study [35,42,43,48]. However, a high SSI and the virtual absence of obvious image artifacts do not alone guarantee that unbiased OCT-A measurement parameters are generated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Esser et al reported that vessel density was not decreased in a rheumatoid arthritis group compared with the control group (p > 0.05) [131]. They concluded that OCTA may not be suitable for early detection of HCQ retinopathy and that the focus should be on intensive and sequential OCT analysis for early detection of HCQ retinopathy [131].…”
Section: Oct Angiographymentioning
confidence: 99%